Outcome of Cadmium on Aminergic System and Protective Function of Vitamin-C - V., Jyostna; G., Anuhya; Managamuri, Ushakiranmayi; K., Srinuvasulu; Poda, Sudhakar (International Journal of Scientific Research in Biological Sciences, 2018)
Cadmium (Cd) is an extremely toxic metal and has a long biological half-life in humans, it enters the brain parenchyma and neurons causing neurological alterations in humans and animal models, leading to lower attention, hyper nociception, olfactory dysfunction and memory deficits. Rats were exposed to low (2mg/kg bw) and high dose (5mg/kg bw) of Cd through subcutaneous injections. The activity levels of epinephrine, norepinephrine and dopamine contents were studied in discrete brain areas of the young rats such as hippocampus, cerebral cortex and cerebellum. Hippocampal levels of catecholamines were significantly reduced in rats exposed to Cd. Our data suggest that Cd exposure disturbs aminergic system in the hippocampus, cerebral cortex and cerebellum and may contribute to the alterations in neurotransmitters.